The Influence of the Connection Properties of Prefabricated Large-Panel Walls on the Static and Dynamic Behavior of a Building - YAVAS, Civan; PAWLAK, Zdzisław Mikołaj (Engineering Transactions, 2023)
The aim of this article is to present a method of assessing the load-bearing capacity of prefabricated large-panel buildings built after the 1950s. Since the main problem in the existing large-panel system buildings is the actual condition of the joints between the panels, it was decided to investigate their impact on the behavior of the entire structure. Therefore, analyses were carried out in which the influence of the adopted connection models on the static and dynamic behavior of the building was examined. Several calculation models of the building were analyzed using three different types of connections between wall and ceiling panels: rigid, elastic and hinged, each representing a distinct state of the actual connection. The criterion used for the comparisons were the values of extreme internal forces and static displacements as well as the dynamic responses of the structure. The parameters that have the greatest influence on the static and dynamic analyses’ results are described and commented on in the conclusion. The analyses’ results are supported by data obtained from source materials: inspection reports, case studies and technical documents. The research helps to understand better the static and dynamic behavior of a building erected using a system of prefabricated large-size panels and to determine the main parameters of the structure influencing this behavior. However, as a result of the research, it was found that changes in the state of panel connection in large-panel system buildings do not have such a significant impact on the overall static and dynamic responses of the structure as initially expected.